Classification of Compounds Words and Indonesian Blends - Sugianto, Riris (MASALIQ, 2021)
This paper is about theoretical research on classification of compound words and Indonesian Blends. Compound and blends are part of words formation in English language. The way to use two words together to yield a new meaning whether blends are one of the many ways new words are made in English. This paper attempts to make the classification of compounds, the reason of why are compounds divided into three categories; solid compound, hypenated compound, and open compound. This paper also attempts to analyze the reason why Indonesian blends inconsistent syllabically and state the implication to the language development